Karakter Personal sebagai Pemoderasi Pengaruh Partisipasi Penganggaran pada Senjangan Anggaran di Bpr Kabupaten Gianyar - Septiana, I Gede Artha; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2018)
Management participation in the budgeting process tends to cause budgetary slack depending on the interests of the management. The purpose of this study is to obtain empirical evidence of the influence of budgetary participation on budgetary slack, and to be able to know the ability of personal character as a moderating variable of influence of budgetary participation in budgetary slack. The research was conducted on 10 BPRs in Gianyar Regency and each BPR was taken by three respondents. The data used in this study is primary data obtained by distributing questionnaires directly to 30 respondents by using purposive sampling technique. Data analysis technique used in this research is Moderated Regression Analysis (MRA). The results of this study suggest that budgetary participation has a positive effect on budgetary slack. Pessimistic personal characters can moderate (reinforce) the influence of budgetary participation on budgetary slack. Keywords: budgetary participation, personal character, budget slack.